Implementasi Ethereum Claims Registry pada Ethereum Blockchain untuk Verifikasi Transaksi Konten Fotografi dengan InterPlanetary File System - Reyner Reyner; Rudy Adipranata; Leo Willyanto Santoso (Jurnal Infra, 2021)
Nowadays, photography often receives a lot of attention from diverse backgrounds. Photography can be used to capture important moments as well as then digitally encased and stored into a storage unit. Typically, photography content is stored on servers, but there are threats in centralized storage like malware attacks, hardware failures and human errors. In the study, Ethereum Claims Registry will be implemented on smart contracts to verify certain attributes about its user which are stored in Ethereum Blockchain, so that users can either issue or retrieve existing claims. Then implementation of the interplanetary file system as a website storage and photography content. Website and Photography Content which are stored on InterPlanetary File System can be accessed globally without centralized storage and do not incur additional fees on ethereum transactions because they are stored off-chain or stored outside the blockchain. Based on the results of the tests that have been carried out, the implementation of the Ethereum Claims Registry and the InterPlanetary File System as a storage for photography content for high gas price requires 0.020518 ETH, medium gas price requires 0.010747 ETH, and low gas requires prices 0.004885 ETH. Then the implementation of the Ethereum Claims Registry obtained 1% ether efficiency on deploying smart contracts, -0.4% on make claims, and -0.4% on set claims